Relação entre imagem corporal e fatores biológicos, sociais e comportamentais : estudo com adolescentes de escolas de tempo integral em Fortaleza-Ce - Araujo, Thabyta Silva de (2016)
The first studies on the body image as a set perception of the appearance that the individual has body in relation to the size and shape image. The study aimed to assess the association between the perceptions of body image and biological, social and behavioral factors. Cross-sectional study with a quantitative approach. The survey was conducted in 2014 with adolescents in all-day schools of the municipal network of Fortaleza-CE of both sexes, aged between 11 and 17 years, attending 7th, 8th and 9th grades. The data collection involved the application of a questionnaire containing questions about biological, social and behavioral factors, the silhouettes of scale and anthropometric measurements. The scale allows to identify the body perception and satisfaction with body image among adolescents through nine silhouettes. We analyzed the data using the chi-square tests for trend proportions, chi-square and linear correlation of Spearman, considering statistically significant analysis with p <0.05. The study was approved under Embodied Opinion No. 301,456. Of 1181 teenagers, 51.5% were male and 48.5% female, prevailing teenagers in the age group of early adolescence, 11-14 years. In the practice of physical activity, 58.0% was considered insufficiently active. In the past year, 78.7% reported not having had sexual intercourse and of sexually active, 40.5% sometimes made use of condoms. Regarding the perception of body image, it was showed a predominance of dissatisfaction among adolescent students. In the perception of body image that represent a healthy body and would like to have (ideal), there was a significant difference between genders (p <0.0001). It was showed that the perception of body image has significant influence factors of school grade (p = 0.005), perception of quality of life and health (p <0.0001) and BMI (p <0.0001), with no influence from any behavioral factor. Even so, the study pointed to the irregular use of condoms by sexually active teenagers in the last year, especially in early adolescence (42.3% sometimes uses and 30.5% never use). It was concluded that more than 75% of adolescent students in all-day schools of the municipal network of Fortaleza-CE reported dissatisfaction in the perception of body image, characterized by the desire to increase silhouette. Thus, it is necessary that the nurse work the theme focusing on health promotion and disease prevention.